Mechanism Study of Cinnamomi Ramulus and Paris polyphylla Sm. Drug Pair in the Treatment of Adenomyosis by Network Pharmacology and Experimental Validation. (16th August 2022) - Zhang, Keke; Zhou, Zhou; Wang, Chuchu; Yu, Mengdie; Zhang, Yiran; Shi, Yaxin; Wang, Xin; Liu, Yang; Xu, Li; Shi, Wei; Liu, Zhiyong
Abstract : Objective . To explore the molecular mechanism of the Cinnamomi ramulus and Paris polyphylla Sm. (C-P) drug pair in the treatment of adenomyosis (AM) based on network pharmacology and animal experiments. Methods . Via a network pharmacology strategy, a drug-component-target-disease network (D-C-T-D) and protein–protein interaction (PPI) network were constructed to explore the core components and key targets of C-P drug pair therapy for AM, and the core components and key targets were verified by molecular docking. Based on the results of network pharmacology, animal experiments were performed for further verification. The therapeutic effect of the C-P drug pair on uterine ectopic lesions was evaluated in a constructed AM rat model. Results . A total of 30 components and 45 corresponding targets of C-P in the treatment of AM were obtained through network pharmacology. In the D-C-T-D network and PPI network, 5 core components and 10 key targets were identified. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that the PI3K signaling pathway was the most significantly enriched nontumor pathway. Molecular docking showed that most of the core components and key targets docked completely. Animal experiments showed that the C-P drug pair significantly ameliorated the pathological changes of endometriotic lesions in AM model rats and inhibited PI3K and Akt gene expression, and PI3K and Akt protein phosphorylation. In addition, treatment with the C-P drug pair promoted AM cell apoptosis; upregulated the protein expression of Bax, Caspase-3, and cleaved Caspase-9; and restrained Bcl-2 expression. Conclusions . We propose that the pharmacological mechanism of the C-P drug pair in the treatment of AM is related to inhibition of the PI3K/Akt pathway and promotion of apoptosis in AM ectopic lesions.